EP610 Investigation of patient acceptability of ctDNA in endometrial cancer follow-up. (1st November 2019) - Relton, A; McDermott, H; Collins, A; Wickham-Joseph, R; Guttery, D; Gorsia, D; Whitton, A; Moss, E
Abstract : Introduction/Background: Circulating tumour DNA (ctDNA) is emerging as a potential option to detect disease recurrence in women undergoing follow-up for endometrial cancer (EC). However, ensuring patient acceptability of changing clinical practice and the introduction of new technology is paramount. Methodology: The aim of this study was to explore women's opinions on the acceptability of ctDNA and their experiences of the ctDNA study. Women undergoing follow-up and participating in a cohort study investigating the utility of ctDNA to detect/monitor recurrent/progressive EC were invited to participate. Semi-structured interviews were conducted by a psychology student (independent from the clinical research team) and analysed through template analysis. Participants were also asked on their views as to the potential role for ctDNA in clinical practice, either in combination with hospital follow-up or as remote monitoring with a patient-initiated follow-up (PIFU) scheme. Results: Women expressed that their motivations behind participating in the study were primarily due to altruism and a desire to help others, including protecting others from having pelvic examinations. Participants spoke about their dislike of the pelvic examinations, which were deemed unpleasant, and shared their desires to 'find a better way', and a blood test was viewed as a welcome alternative. The ctDNA blood test was viewed as more physically and psychologically acceptable than the current clinical examination. Participants expressed a wish to know if their ctDNA level was raised, even if a recurrence wasn't detectable on imaging, because it was felt that they would have more certainty in their likelihood of recurrence. Conclusion: This study provides in-depth insights into patient views on the acceptability of ctDNA for monitoring of EC, with women stating an overwhelming preference for a blood test over pelvic examination. Participant insights also revealed that PIFU in conjunction with ctDNA, appears to be an acceptable new approach to EC follow-up. Disclosure: Nothing to disclose.